Lung response to congenitally athymic (nude), heterozygous, and Swiss Webster mice to aerogenic and intranasal infection by Nocardia asteroides. - Beaman, B L (1978)
Congenitally athymic (nude, Nu/Nu), heterozygous (Nu/+), and Swiss Webster mice were exposed to virulent Nocardia asteroides GUH-2 inhaled from aerosols or administered intranasally. Clearance of the bacteria from the lungs was determined at 6 h and 1, 2, 3 and 7 days after infection. N. asteroides aspirated into the lungs from intranasal administration were killed less rapidly and induced more severe pulmonary infections than did comparable numbers of organisms inhaled from aerosols. Bacterial clearance and histological data indicated that nude mice were significantly more susceptible to nocardial infection than were heterozygous littermates or Swiss Webster mice. From these data we conclude that: (i) pulmonary defenses cope less well with intranasally administered N. asteroides than with aerosolized organisms, (ii) alveolar macrophages alone appear not to be an efficient barrier to nocardial infections, and (iii) T cells are important to pulmonary clearance and prevention of dissemination of N. asteroides from the lung.